2016
DOI: 10.1007/s11248-016-9937-5
|View full text |Cite
|
Sign up to set email alerts
|

Comparison of BALB/c and B6-albino mouse strain blastocysts as hosts for the injection of C57BL6/N-derived C2 embryonic stem cells

Abstract: Embryonic stem (ES) cells from a C57BL/6N (B6N) background injected into B6(Cg)-Tyrc-2J/J (B6-albino) recipient blastocysts are commonly used for generating genetically modified mouse models. To understand the influence of the recipient blastocyst strain on germline transmission, BALB/cAnNTac and B6-albino germline transmission rates were compared using the C57BL6/N-derived C2 ES cell line. A total of 92 ES cell clones from 27 constructs were injected. We compared blastocyst yield, birth rate, chimera formatio… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

2
7
0
1

Year Published

2016
2016
2022
2022

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(10 citation statements)
references
References 15 publications
2
7
0
1
Order By: Relevance
“…In our experiments, the B6NTac host strain produced more injectable blastocysts per female after superovulation than the B6 albino strain; this finding was consistent with a previous report that described a poor superovulation response in B6 albinos (Schuster-Gossler et al 2001). Furthermore, the number of injectable B6 albino embryos per female was higher than the number (3.6 per fermale) reported by Alcantar et al (2016). This major difference may be related to the host age and the embryo collection method.…”
Section: Discussionsupporting
confidence: 91%
See 1 more Smart Citation
“…In our experiments, the B6NTac host strain produced more injectable blastocysts per female after superovulation than the B6 albino strain; this finding was consistent with a previous report that described a poor superovulation response in B6 albinos (Schuster-Gossler et al 2001). Furthermore, the number of injectable B6 albino embryos per female was higher than the number (3.6 per fermale) reported by Alcantar et al (2016). This major difference may be related to the host age and the embryo collection method.…”
Section: Discussionsupporting
confidence: 91%
“…Over recent years, there has been a significant increase in the use of B6N-derived ES cells to produce KO mice. Differing combinations of host embryos and ES cells leads to variation in the ability to produce KO mice (Alcantar et al 2016;Keskintepe et al 2007;Pettitt et al 2009;Schuster-Gossler et al 2001;Ware et al 2003), however, the mechanism underlying these findings remains unclear at present. To develop an efficient and easily applicable method to produce KO mice, we compared the efficiency of two widely applied hosts (B6 albino and B6NTac) with regards to the microinjection of B6N (JM8A3.N1) ES cells to generate KO mice.…”
Section: Discussionmentioning
confidence: 99%
“…In one study, ES cell chimaeras with a large ES cell contribution were produced more efficiently if ES cells were combined with BALB/c blastocysts, from unsuperovulated 12-week-old females, rather than C57BL/6-albino or BALB/c blastocysts from females superovulated at 4 weeks ( Esmail et al, 2016 ). Although this did not distinguish the effects of genotype, maternal age and induced superovulation, another study showed that BALB/c blastocysts were superior to C57BL/6-albino blastocysts for chimaera production with C57BL/6N-derived ES cells, when all the embryos were produced by females superovulated at 3-4 weeks ( Alcantar et al, 2016 ). Although C57BL/6-albino females produced more blastocysts, use of BALB/c host blastocysts produced a higher birth rate, a higher yield of chimaeras, more male chimaeras with a high ES cell contribution and a higher rate of germline transmission of the ES cell genotype.…”
Section: Discussionmentioning
confidence: 98%
“… Alcantar et al (2016) suggested that BALB/c strain embryos might provide a less competitive host environment than C57BL/6-albino embryos and so allow the C57BL/6N ES cells to contribute better to ES cell chimaeras. If BALB/c host blastocysts lagged behind C57BL/6-albino host blastocysts, this might allow more extensive colonisation by ES cells, even if BALB/c cells did not continue to divide more slowly.…”
Section: Discussionmentioning
confidence: 99%
“…Не менее важную роль для рождения большого чис-ла фертильных химерных животных играет сочетание генотипов ЭС клеток, бластоцист и приемных матерей, поэтому постоянно ведутся поиски оптимальных комби-наций этих факторов (Seong et al, 2004;Fielder et al, 2012;Alcantar et al, 2016).…”
Section: Discussionunclassified